PROBLEM-BASED LEARNING AS AN INSTRUCTIONAL STRATEGY FOR STRENGTHENING STUDENTS’ LITERACY AND NUMERACY SKILLS: A SYSTEMATIC LITERATURE REVIEW: Pembelajaran Berbasis Masalah sebagai Strategi untuk Memperkuat Kemampuan Literasi dan Numerasi Siswa: Tinjauan Literatur Sistematis - Iid Maulidiyah Subhi; Riris Widiyanti Putri; Siti Mahmudah; Ichsan Anshory; Arina Restiani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The rapid advancement of technology and globalization requires educational systems to equip students with strong literacy and numeracy competencies as foundational skills for critical thinking and problem-solving. However, international assessments such as PISA indicate that Indonesian students’ literacy and numeracy performance remains relatively low. This study aims to examine the role of Problem-Based Learning (PBL) as an instructional approach for enhancing students’ literacy and numeracy skills. This research employs a literature review method by systematically analyzing relevant national and international journal articles obtained from databases such as Google Scholar, SINTA, and indexed international publishers. The analysis focuses on the conceptual framework of literacy and numeracy, the characteristics and syntax of the PBL model, and key factors influencing its implementation in classroom practice. The findings indicate that Problem-Based Learning effectively promotes literacy and numeracy development through student-centered, collaborative, and contextual learning processes. PBL engages students in interpreting textual and numerical information, analyzing real-world problems, processing data, and communicating solutions logically. Teachers function as facilitators who guide inquiry, encourage critical reflection, and support meaningful learning experiences. This study concludes that Problem-Based Learning represents a sustainable instructional strategy for strengthening literacy and numeracy competencies and fostering a culture of critical thinking in contemporary education.